Evaluation of medical physics training in radiology residency in 67 countries. (October 2018) - Rehani, Madan M.; Pauwels, Ruben; Rehani, Bhavya
Highlights: Teaching of medical physics to radiology resident by radiologists is common. Lack of involvement of medical physicists in the examinations observed. Better involvement of medical physicists in radiology education needed. Abstract: Purpose: The main aim of medical physics training in radiology residency is to have appropriate and safer imaging of patients and safety of personnel. The need to have adequate coverage of medical physics and radiation safety in curricula of radiology residency is well perceived, but it is not known how far it is implemented in practice. Methods: We have analysed the data from 67 countries on medical physics teaching and assessment of residents in radiology programs, considering differences between countries in function of their human development index (HDI). Results: The results indicate that teaching of medical physics by radiologists rather than by medical physicists is very common and there is relationship with the developmental status of a country. The majority of countries with very high HDI used a written test (69%) for medical physics topics, often in combination with other subjects (63%). Further, there is lack of direct involvement of medical physicists during the examination phase of residents. Geographically, it can be seen that Latin American countries in particular lack involvement of medical physicists during both the teaching and examination phase. Conclusion: The lack of adequate involvement of medical physicists in training and in the formal examination of radiology residents in both developed and developing countries is a matter of concern with likely implications on patient and staff safety.